Functionalization of L-Cystein On Magnetite As Magnetic Adsorbent Metals for SDG 14 - Amaria Amaria; Dina Kartika Maharani; Amalia Putri Purnamasari; Sari Edi Cahyaningrum; Aisha Setiyanti (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The increasing consumption of gold (Au) in the electronics, catalysis, and medical sectors has led to the depletion of primary ore resources while increasing the accumulation of electronic waste (e-waste) which reaches 62 million tons per year globally. Therefore, the development of selective, efficient, and environmentally friendly Au(III) recovery technology from secondary sources is very urgent. This study aims to synthesize and characterize magnetic adsorbents based on magnetite (Fe3O4@Cys) functionalized with L-Cysteine (Fe3O4@Cys) and evaluate its performance in the recovery of Au(III) ions from aqueous solutions. Method: L-Cysteine was chosen because it contains a thiol group (-SH) which has a high affinity for Au(III) based on the hard-soft acid-base (HSAB) theory. The synthesis was conducted through silica coating followed by L-cysteine immobilization using GPTMS as a coupling agent. Results: FTIR analysis confirmed the presence of Fe–O, Si–O–Si, and Si–OH groups, indicating successful functionalization. XRD results showed that the magnetite crystal structure was retained after modification, with a crystallite size of 16.43 nm and the presence of amorphous silica. Novelty: The synthesized Fe3O4@Cys exhibited good acid stability, demonstrating its potential as a selective magnetic adsorbent for Au(III) recovery from secondary resources.